LITERASI KESEHATAN PASIEN DIABETES MELLITUS PESERTA PROLANIS DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU TAHUN 2019 - Aulia Sekar Chairunnisa; Tiara Fani (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
As a result of low health literacy levels, patients will face more challenges when they access and use the health care service system. This research purpose is to know about literacy levels based on a patient's characteristics and their activities in the Program of Chronic Disease Management (PROLANIS). The researcher did the descriptive research by using the HLS-EU-Q16 questionnaire which was adapted in the Indonesian language. Respondents in this study were 20 Diabetes Mellitus Patients in Prolanis Participants in 2020. The result of the research showed that the respondents who live in the Kedungmundu Primary Healthcare Center (PHC) area mostly were elderly (55%), female (55%), high school graduates (50%), have a job (50%). PROLANIS activities followed by the respondent are medical consultation (100%), education program (100%), and gymnastic (90%). Health literacy categories were Inadequate HL (35%), Problematic HL (50%), and Sufficient HL (15%). This result shows the extra need for handling people with Diabetes Mellitus, especially for the elderly. It should be important to monitor a patient's blood sugar and to educate the patients for better self-management.Keywords: diabetes mellitus, literasi kesehatan, prolanis